Genetic and Functional Evidence Supports LPAR1 as a Susceptibility Gene for Hypertension. Issue 3 (September 2015) - Xu, Ke; Ma, Lu; Li, Yang; Wang, Fang; Zheng, Gu-Yan; Sun, Zhijun; Jiang, Feng; Chen, Yundai; Liu, Huirong; Dang, Aimin; Chen, Xi; Chun, Jerold; et al.
<x xml:space="preserve">Abstract</x> Essential hypertension is a complex disease affected by genetic and environmental factors and serves as a major risk factor for cardiovascular diseases. Serum lysophosphatidic acid correlates with an elevated blood pressure in rats, and lysophosphatidic acid interacts with 6 subtypes of receptors. In this study, we assessed the genetic association of lysophosphatidic acid receptors with essential hypertension by genotyping 28 single-nucleotide polymorphisms from genes encoding for lysophosphatidic acid receptors, LPAR1, LPAR2, LPAR3, LPAR4, LPAR5, and LPAR6 and their flanking sequences, in 3 Han Chinese cohorts consisting of 2630 patients and 3171 controls in total. We identified a single-nucleotide polymorphism, rs531003 in the 3′-flanking genomic region of LPAR1, associated with hypertension (the Bonferroni corrected P=1.09×10–5, odds ratio [95% confidence interval]=1.23 [1.13–1.33]). The risk allele C of rs531003 is associated with the increased expression of LPAR1 and the susceptibility of hypertension, particularly in those with a shortage of sleep (P=4.73×10–5, odds ratio [95% confidence interval]=1.75 [1.34–2.28]). We further demonstrated that blood pressure elevation caused by sleep deprivation and phenylephrine-induced vasoconstriction was both diminished in LPAR1-deficient mice. Together, we show that LPAR1 is a novel susceptibility gene for human essential hypertension and that stress, such as shortage of sleep, increases the susceptibility of patients with risk allele to essential hypertension.